Supply Chain Strategy in Stabilization of Products Price: Case Study Beef Price in Indonesia - Ihwan Susila; Bambang Setiaji; Henri D. Wahyudi; Anton A. Setyawan (International Journal of Supply Chain Management, 2020)
Abstract— This research explores how the breeders, brokers, wholesalers, and retailers, along the supply chain of beef market; contribute to the beef price volatility. This study conceptualizes the policy of beef price stabilization that affected by beef production level, market structure, and government intervention. Using phenomenological approach, the findings highlight that price volatility commences from the beef supply response and market structure. A total of 18 in-depth interviews were conducted to gain insight into the complexity of the beef price formation specifically to capture and understand this phenomenon from the breeders ‘point of views, the sellers, and the government. Purposive sampling was adopted to select participants to provide enough depth and riches to the unique experiences of the phenomena in Surakarta district, Indonesia. The experience of Surakarta City in maintaining the stability of beef price has implications both nationally and globally. This price stabilization model can be adopted by other regions and even other countries that still rely on imported beef. Surakarta is not a beef-producing agricultural area. The five research findings are important to serve as a lending model of effort in beef price stabilization. This applies also in maintaining supply availability. In a country, beef imports by the private sector are beneficial to beef buyers, especially at relatively low international period prices and stable. In periods of unstable global markets with high prices, communication and coordination, in larger cases, timely intervention and clear policy messages are needed in avoiding the buildup of private stocks. This is a precaution that can greatly aggravate the rise in domestic prices. This research focus on the beef price stabilization. However, the bargaining position of buyer and supplier has not identified. Future research need to explore how the level of information received by some actors in the supply chain. The government can use this research finding to maintain the price to be stabled and apply the policies through aspects of sustainability. This research contributes to provide the stabilization model of beef price stabilization in the supply chain framework.